INTELLECTUAL CAPITAL PADA KINERJA KEUANGAN PERUSAHAAN - Mishelei Loen, SE., M.Si.; Mulia Rahmah; Yessy Kusumadewi (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study aims to determine the effect between Intellectual Capital proxied by three components namely human capital, structural capital, and capital employed on the Company's Financial Performance. The type of research used in this research is quantitative research. The population used in this study are transportation sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019 to 2023. Data obtained from the Indonesia Stock Exchange website www.idx.co.id. The data in this study were processed using SPSS version 22 software for statistics, using purposive sampling method. The results obtained in this study Human Capital and Capital Employed have no effect on Return on Asset. Structural Capital affects Return on Asset (ROA). Human Capital, Structural Capital, and Capital Employed together have no effect on Return on Asset (ROA). The implication of this research is that companies should pay more attention to ideal indicators for each component of intellectual capital that can improve the company's financial performance